Lithium battery positive electrode material as well as preparation method and application thereof
By preparing a lithium battery cathode material with the general chemical formula LiaNixCoyMzNpO2, and using a sintering method of sheet-like precursors with lithium source and lanthanide modifiers, a structure is formed in which long strip-shaped primary particles are arranged radially along secondary microspheres. This solves the problem of insufficient capacity and rate performance of ternary cathode materials and enables the application of high-performance lithium batteries.
Patent Information
- Application Number
- CN202410550443.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2025-11-11
AI Technical Summary
Existing layered ternary cathode materials suffer from low capacity and poor rate performance in lithium batteries, especially at high rates where the migration rates of lithium ions and electrons are limited, making it difficult to meet the requirements of high-performance lithium batteries.
Using lithium-ion battery cathode material with the general chemical formula LiaNixCoyMzNpO2, the crystallization process of lithium-ion battery cathode material is optimized by mixing a sheet-like cathode material precursor with a lithium source and a lanthanide element modifier, followed by programmed temperature sintering to form a structure in which elongated primary particles are arranged radially along secondary microspheres.
This improves the discharge specific capacity and rate performance of lithium battery cathode materials, enabling high energy density and high power lithium battery applications, and possessing high first-cycle efficiency and excellent electrochemical performance.
Smart Images

Figure CN120933364A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium batteries, specifically to a lithium battery cathode material, its preparation method, and its application. Background Technology
[0002] New energy vehicles are an important means to achieve the "dual-carbon" green development goal. With the promotion and popularization of new energy vehicles, the market demands increasingly higher performance from electric vehicles, especially in terms of driving range and fast charging / discharging. The key to electric vehicles is the power battery, and its performance determines the overall performance of the vehicle. Cathode materials are one of the key components of power batteries, determining crucial indicators such as energy density and charge / discharge rate. Currently, commercially available cathode materials mainly include olivine-structured LiFePO4, spinel-structured LiMn2O4, layered LiCoO2, and layered ternary cathode materials. Among these cathode materials, layered ternary cathode materials have higher theoretical capacity and, when applied to lithium batteries, can improve the driving range of electric vehicles, making them a research hotspot for high-performance lithium battery cathode materials.
[0003] However, the actual capacity of layered ternary cathode materials is not high, especially at higher rates. Due to the limited lithium-ion and electron migration rates, the capacity that can be utilized is even lower, resulting in poor rate performance. To improve the above-mentioned problems of ternary cathode materials, CN103474628B describes carbon coating on the surface of ternary cathode materials, where conductive carbon and ternary cathode materials are simultaneously coated in a network of amorphous carbon. The amorphous carbon acts as a conductive medium between the conductive carbon and the ternary cathode materials, thus improving the rate performance of the ternary cathode materials. CN104993100A discloses modifying the surface of ternary cathode materials with carbon nitride nanotubes to improve the rate performance of the materials. However, these methods do not involve improving the structure of the ternary cathode materials themselves, and therefore cannot fundamentally improve the discharge capacity and rate performance of ternary cathode materials. Summary of the Invention
[0004] This invention addresses the problems of low capacity and poor rate performance of existing ternary cathode materials by providing a lithium-ion battery cathode material, its preparation method, and its applications. The lithium-ion battery cathode material of this invention has advantages such as high discharge specific capacity, high first-cycle efficiency, and good rate performance.
[0005] The first aspect of this invention provides a lithium battery cathode material, wherein the general chemical formula of the cathode material is Li. a Ni x Co y M z N pO2, where 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality. M is selected from at least one element of Group VIIB or Group IIIA, N is selected from at least one of the lanthanide elements. The primary particles of the positive electrode material are elongated, and the width of the elongated shape is 0.15 - 5.00 μm.
[0006] In the above technical solution, the chemical general formula of the positive electrode material is Li a Ni x Co y M z N p O2, 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, where the values of x, y, and z are not all 0 at the same time. Preferably, the values of x, y, and z are all non-zero, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality.
[0007] In the above technical solution, the morphology of the positive electrode material is secondary microspheres formed by the aggregation of primary particles, and the primary particles are arranged along the radial direction of the secondary microspheres. Further, for the primary particles, the width of the elongated shape is preferably 0.20 - 5.00 μm, and more preferably 0.30 - 3.00 μm.
[0008] In the above technical solution, the aspect ratio of the primary particles is 1.05 - 15.00, preferably 1.30 - 10.00, and more preferably 1.50 - 8.00.
[0009] In the above technical solution, the median size of the secondary microspheres is 1.0 - 20.0 μm. Here, the median size represents the particle diameter corresponding to when the cumulative particle size distribution percentage of spherical particles reaches 50%.
[0010] In the above technical solution, the element of Group VIIB is preferably Mn, the element of Group IIIA is preferably Al, M is preferably at least one of Mn and Al, and the lanthanide elements are selected from at least one of Sm, Eu, and Gd.
[0011] The second aspect of the present invention provides a preparation method of the above lithium battery positive electrode material, including:
[0012] Mixing a positive electrode material precursor, a lithium source, and a modifier containing a lanthanide element, and sintering to obtain the lithium battery positive electrode material.
[0013] In the above technical solution, the chemical general formula of the positive electrode material precursor is Ni x Co y M z(OH)2, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, and the values of x, y and z are not all 0 at the same time, and the values of x, y and z satisfy the principle of electroneutrality.
[0014] In the above technical solution, the morphology of the cathode material precursor is microspheres formed by the stacking of sheets. The average thickness of the sheets is 1-500 nm, preferably 10-300 nm.
[0015] In the above technical solution, the lithium source is preferably selected from at least one of lithium nitrate (LiNO3), lithium chloride (LiCl), lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium hydroxide monohydrate (LiOH·H2O), lithium oxide (Li2O), lithium acetate (CH3COOLi), and lithium oxalate (Li2C2O4).
[0016] In the above technical solution, the molar ratio of the cathode material precursor to the lithium source (calculated as Li element) is 1:(0.90-1.20), preferably 1:(1.00-1.20).
[0017] In the above technical solution, the lanthanide-containing modifier is preferably selected from at least one of lanthanide-containing nitrates, chlorides, carbonates, hydroxides, oxides, acetates, and oxalates.
[0018] In the above technical solution, the molar ratio of the cathode material precursor and the lanthanide-containing modifier, based on the lanthanide elements, is 1:(0-0.10) and not 0, preferably 1:(0.001-0.05), and more preferably 1:(0.005-0.05).
[0019] In the above technical solution, the sintering is programmed temperature sintering, the heating rate is preferably 0.5-10℃ / min, the sintering temperature is 600-1000℃, preferably 720-900℃, and the sintering time is 4-48h, preferably 8-24h, and more preferably 12-20h.
[0020] In the above technical solution, pre-sintering is performed before sintering. Pre-sintering is programmed temperature rise sintering, with a preferred heating rate of 0.5-10℃ / min, a pre-sintering temperature of 300-600℃, preferably 400-550℃, more preferably 450-530℃, and a pre-sintering time of 1-10h, preferably 4-8h.
[0021] The third aspect of this invention provides the application of the above-mentioned lithium battery cathode material in lithium batteries.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The lithium battery cathode material of this invention is a secondary microsphere formed by the aggregation of primary particles along the radial direction of spherical particles. The primary particles are elongated strips with a width of 0.15-5.00 μm. The lithium battery cathode material of this invention exhibits excellent electrochemical performance, with advantages such as high discharge specific capacity, high first-cycle coulombic efficiency, and good rate performance.
[0024] 2. In the preparation process of the lithium battery cathode material of the present invention, a plate-shaped cathode material precursor, a lithium source, and a lanthanide modifier are mixed and sintered. During the sintering process, the crystallization process of the primary particles of the lithium battery cathode material is regulated by the synergistic effect of the plate-shaped precursor, the lanthanide modifier, and the control of the sintering temperature and sintering time. The resulting primary particles of the lithium battery cathode material have an elongated shape and are arranged along the radial direction of the secondary microspheres of the lithium battery cathode material. The elongated shape is relatively wide. This composition and structure of the material is more conducive to the diffusion of lithium ions and can improve the discharge specific capacity and rate performance of the material.
[0025] 3. The lithium battery cathode material provided by this invention can be used in high energy density and high power lithium batteries, and has a high discharge specific capacity and excellent rate performance. The discharge specific capacity at 1C rate can reach 179.4mAh / g. Attached Figure Description
[0026] Figure 1 This is a SEM image of the lithium battery cathode material prepared in Example 1 of the present invention;
[0027] Figure 2 This is a SEM image of a cross-section of the lithium battery cathode material prepared in Example 1 of this invention. Detailed Implementation
[0028] The technical solution of the present invention will be described in detail below.
[0029] The first aspect of this invention provides a lithium battery cathode material, wherein the general chemical formula of the lithium battery cathode material is Li. a Ni x Co y M z N p O2, M is selected from at least one element of Group VIIB or Group IIIA, and N is selected from at least one lanthanide element.
[0030] The lithium battery cathode material provided by this invention has the general chemical formula Li. a Ni x Co y M z N pCompounds of O2, where 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, preferably 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, more preferably 0.5 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, the values of x, y, and z are not all 0 at the same time, preferably the values of x, y, and z are all not 0, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality.
[0031] In one embodiment of the present invention, preferably, M is selected from Mn and / or Al. That is, preferably, Li a Ni x Co y M z N p O2 is Li a Ni x Co y Mn z N p O2 or Li a Ni x Co y Al z N p O2.
[0032] The positive electrode material for lithium batteries provided by the present invention is a secondary microsphere formed by the aggregation of primary particles, and the primary particles are arranged along the radial direction of the secondary microsphere, and the median particle size of the secondary microsphere is 1.0 - 20.0 μm.
[0033] The lithium battery cathode material provided by this invention comprises primary particles in the form of elongated strips. The aspect ratio of the primary particles is 1.05-15.00, preferably 1.30-10.00, and more preferably 1.50-8.00. The aspect ratio of the primary particles is, for example, but not limited to, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.95, 2.20, 2.45, 2.70, 2.95, 3.20, 3.45, 3.70, 3.95, 4.20, 4.45, 4.70, 4.95, 5.20, 5.45, 5.70, 5.95, 6.20, 6.45, 6.70, 6.95, 7.20, 7.45, 7.70, 7.95, 8.00, and any value within the range formed by any two of these values. The width of the primary particles is 0.15-5.00 μm, preferably 0.20-5.00 μm, more preferably 0.30-3.00 μm, for example, but not limited to, 0.30 μm, 0.35 μm, 0.40 μm, 0.45 μm, 0.50 μm, 0.55 μm, 0.60 μm, 0.70 μm, 0.80 μm, 0.90 μm, 1.00 μm, 1.50 μm, 2.00 μm, 2.50 μm, 3.00 μm, etc., and any value within the range formed by any two of these values.
[0034] In a preferred embodiment of the present invention, the SEM image of the lithium battery cathode material is as follows: Figure 1 As shown. From Figure 1 As can be seen from the image, the lithium battery cathode material of this invention consists of spherical secondary particles with a medium particle size of 9.6 μm. The SEM image of a cross-section of the lithium battery cathode material is shown below. Figure 2 As shown. From Figure 2 As can be seen, the primary particles are elongated and wide, with an average width of 1.05 μm. Furthermore, the elongated primary particles are arranged along the radial direction of the secondary microspheres, and the average aspect ratio of the elongated primary particles is 3.83.
[0035] In this invention, the scanning electron microscope (SEM) images were obtained using a ZEISS Merlin model scanning electron microscope from the German company ZEISS.
[0036] Through in-depth research on lithium battery cathode materials, the inventors of this invention have creatively obtained lithium battery cathode materials with the above-mentioned composition and structural characteristics during the preparation of lithium battery cathode materials. Lithium battery cathode materials with this characteristic composition and structure have higher discharge specific capacity, first-cycle coulombic efficiency and rate performance, and can be used in high-performance lithium batteries.
[0037] A second aspect of the present invention provides a method for preparing the above-mentioned lithium battery cathode material, comprising:
[0038] The cathode material precursor, lithium source, and lanthanide-containing modifier are mixed and sintered to obtain the lithium battery cathode material.
[0039] In this invention, the general chemical formula of the cathode material precursor is Ni. x Co y M z (OH)₂, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, and more preferably 0.5≤x≤0.8, 0≤y≤0.5, 0≤z≤0.5, where x, y, and z are not simultaneously 0, and the values of x, y, and z satisfy the principle of electroneutrality. As a non-limiting example, a typical chemical composition of the precursor could be Ni. 0.5 Co 0.2 Mn 0.3 (OH)2, Ni 0.6 Co 0.2 Mn 0.2 (OH)2, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, Ni 0.9 Co 0.05 Mn 0.05 (OH)2, Ni 0.95 Co 0.025 Mn 0.025 (OH)2, Ni 0.8 Co 0.15 Al 0.05 (OH)2, etc. The morphology of the cathode material precursor is a microsphere formed by the stacking of sheets, the thickness of which is 1-500 nm, preferably 10-300 nm. The thickness of the sheets is, for example, but not limited to, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 220 nm, 250 nm, 270 nm, 300 nm, and any value within the range formed by any two of these values.
[0040] In this invention, the lithium source may exist in the form of a lithium salt, which is preferably selected from at least one of lithium nitrate (LiNO3), lithium chloride (LiCl), lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium hydroxide monohydrate (LiOH·H2O), lithium oxide (Li2O), lithium acetate (CH3COOLi), and lithium oxalate (Li2C2O4).
[0041] In this invention, the mixing of the cathode material precursor and the lithium source can be achieved by means of a high-speed mixer, ball mill, V-type mixer, mechanical stirring, plow mixer, double helix conical mixer, etc.
[0042] In this invention, the molar ratio of the cathode material precursor to the lithium source (calculated as Li) is 1:(0.90-1.20). As a non-limiting example, when the number of moles of the precursor is 1, the number of moles of the lithium source (calculated as Li) can be 0.90, 0.95, 1.00, 1.01, 1.03, 1.05, 1.10, 1.15, 1.20, or any value within the range formed by any two of these values.
[0043] In this invention, the lanthanide-containing modifier is preferably selected from at least one of lanthanide-containing nitrates, chlorides, carbonates, hydroxides, oxides, acetates, and oxalates. As a non-limiting example, the lanthanide-containing modifier may be at least one of samarium nitrate, europium oxalate, gadolinium chloride, samarium oxide, europium hydroxide, gadolinium carbonate, and samarium chloride.
[0044] In this invention, the molar ratio of the cathode material precursor to the lanthanide-containing modifier (calculated as lanthanides) is 1:(0-0.10) and not 0. As a non-limiting example, when the number of moles of the precursor is 1, the number of moles of the lanthanide-containing modifier can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, or any value within any range of any two of these values. Preferably, the molar ratio of the precursor to the lanthanide-containing modifier (calculated as lanthanides) is 1:(0.001-0.05).
[0045] In this invention, sintering is carried out in an atmosphere furnace, and the sintering atmosphere can be at least one of air, oxygen, and an inert atmosphere (such as nitrogen).
[0046] In this invention, the sintering is programmed temperature sintering, and the sintering temperature is 600-1000℃, for example, it can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, or any range between any two values. More preferably, the calcination temperature is 720-900℃. The sintering time is 4-48h, for example, it can be 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h, or any range between any two values. Preferably, the sintering time is 8-24h, and more preferably, the sintering time is 12-20h.
[0047] In this invention, pre-sintering is performed before sintering. The pre-sintering temperature is 300-600℃, for example, it can be any range of 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, or any two of these values. Preferably, the sintering temperature is 400-550℃, and more preferably, the pre-sintering temperature is 450-530℃. Preferably, the pre-sintering time is 1-10h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or any two of these values. More preferably, the pre-sintering time is 4-8h.
[0048] In this invention, there is no particular limitation on the heating rate of sintering, but it is preferably 0.5-10℃ / min, for example 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 5℃ / min, 10℃ / min, and any value within the range formed by any two of these values.
[0049] In this invention, there are no special restrictions on the mixing of the cathode material precursor, lithium source, and lanthanide-containing modifier, and it can be achieved by means of high-speed mixer, ball mill, V-type mixer, mechanical stirring, plow mixer, double helix conical mixer, etc.
[0050] The third aspect of the present invention provides a lithium battery cathode material prepared by the preparation method described above.
[0051] The properties of the lithium battery cathode material have already been described in detail in the first aspect and will not be repeated here.
[0052] A fourth aspect of the present invention provides the application of the lithium battery positive electrode material as described above in a lithium battery. The lithium battery comprises: a positive electrode, including the aforementioned lithium battery positive electrode material; a negative electrode; an electrolyte; and a separator. The positive and negative electrodes can be prepared by coating and drying a composite for forming a layer containing a positive electrode active material and a composite for forming a layer containing a negative electrode active material onto their respective current collectors.
[0053] Positive electrode composites can be prepared using positive electrode active materials, conductive agents, binders, and solvents.
[0054] This invention does not impose specific limitations on the conductive agent, as long as it is conductive and remains stable within the charge-discharge range. The conductive agent can be at least one of acetylene black, Ketjen black, artificial graphite, natural graphite, carbon nanotubes, graphene, superconducting carbon, carbon nanofibers, carbon dots, aluminum powder, nickel powder, titanium dioxide, and conductive polymers.
[0055] The binder provides adhesion between the positive electrode active material, the conductive agent, and the current collector. The binder can be at least one of the following: polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), waterborne acrylic resin, polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate (EVA), vinylidene fluoride-tetrafluoroethylene-propylene lithium battery copolymer, vinylidene fluoride-hexafluoroethylene-tetrafluoroethylene lithium battery polymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylic resin.
[0056] This invention does not impose specific limitations on the current collector, as long as it has suitable conductivity. The current collector can be made of aluminum, nickel, copper, titanium, silver, stainless steel, or carbon materials. The current collector can be processed into various forms such as foil, sheet, film, mesh, perforated, or nonwoven fabric.
[0057] The solvent can be N-methylpyrrolidone.
[0058] Anode composites can be prepared using anode active materials, conductive agents, binders, and solvents.
[0059] This invention does not impose any special restrictions on the negative electrode active material, and it can be selected according to actual needs. The negative electrode active material can be at least one of the following: artificial graphite, natural graphite, soft carbon, hard carbon, mesophase microspheres (MCMB), carbon fiber, lithium metal, silicon, silicon oxide, lithium metal alloy, and lithium titanate.
[0060] The conductive agent and binder of the negative electrode in this invention are not particularly limited and can be of the same type and content as those used in the preparation of the positive electrode. The current collector of the negative electrode can also be made of aluminum, nickel, copper, titanium, silver, stainless steel, and carbon materials. The current collector can also be processed into various forms such as foil, sheet, film, mesh, perforated, and non-woven fabric.
[0061] The electrolyte of this invention is a liquid electrolyte containing lithium salt and solvent, wherein the lithium salt and solvent are not specifically limited.
[0062] The solvent can be a non-aqueous solvent, such as at least one of ethylene carbonate (EC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), propylene carbonate (PC), ethyl propyl carbonate (EPC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), methyl formate (MF), ethyl formate (Eft), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), and propyl butyrate (BP).
[0063] The lithium salt can be at least one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium bis(oxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalate phosphate), and LiTFOP (lithium tetrafluorooxalate borate).
[0064] To improve the performance of lithium batteries, additives can be selectively added to the electrolyte, such as at least one of the following: vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), tris(trimethylsilane) phosphate (TMSP), sulfonate cyclic quaternary ammonium salts, ethylene sulfite (DTO), dimethyl sulfite (DMS), 1-propene-1,3-sulfonyl lactone (PST), 4-propyl ethylene sulfate (PEGLST), diethyl sulfite (DES), adiponitrile (ADN), succinate (SN), 1,3-propane sulfonyl lactone (1,3-PS), vinyl sulfate (DTD), and 4-methyl ethylene sulfate (PCS).
[0065] A separator is placed between the positive and negative electrodes to isolate them. The separator can be made of polyolefins, such as polyethylene, polypropylene, or a composite of polyethylene and polypropylene, or it can be a sheet formed of glass fiber or a non-woven fabric. When using a solid electrolyte, the solid electrolyte can also be used as the separator.
[0066] The following describes the preparation method of the lithium battery, used to prepare the aforementioned lithium battery. The main steps include: uniformly mixing the lithium battery positive electrode material, conductive agent, binder and solvent, coating it onto at least one surface of the positive electrode current collector, drying, rolling and slicing it for use as the positive electrode; uniformly mixing the negative electrode material, conductive agent, binder and solvent, coating it onto at least one surface of the negative electrode current collector, drying, rolling and slicing it for use as the negative electrode; assembling the positive electrode sheet, separator and negative electrode sheet into a stacked or wound cell, placing the cell in a casing, injecting electrolyte and encapsulating it to obtain the lithium battery.
[0067] In the above-mentioned positive or negative electrode sheets, the amount of positive and negative electrode materials, conductive agents, and binders is not specifically limited. For example, based on the total amount of positive or negative electrode materials, the mass content of the lithium battery positive or negative electrode materials can be 50%-99%, the mass content of the conductive agent can be 0.5%-25%, and the mass content of the binder can be 0.5%-25%.
[0068] For comparison, in the embodiments of the present invention, the mass ratio of the positive electrode material of the lithium battery, the conductive agent, and the binder is 92:3:5. The conductive agent is acetylene black, the binder is polyvinylidene fluoride (PVDF), the negative electrode in the coin cell is metallic lithium, the separator is American Celllgard 2400 polypropylene separator, the electrolyte is liquid electrolyte, the solvent is a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a volume ratio of 3:7, the solute is lithium hexafluorophosphate (LiPF6) with a molar concentration of 1 mol / L.
[0069] The lithium batteries in this embodiment of the invention are assembled in an inert atmosphere glove box, where the moisture and oxygen content is below 0.1 ppm. There are no particular limitations on the battery model; for comparison, the coin cell model used in this embodiment is the 2025 type, and the electrochemical testing conditions are: temperature 25°C; voltage range 2.8-4.3V.
[0070] The present invention will be described in detail below through embodiments.
[0071]
Example 1
[0072] This embodiment is used to illustrate the method for preparing and evaluating lithium battery cathode materials according to the present invention.
[0073] (1) Preparation of lithium battery cathode materials
[0074] Take the chemical composition as Ni 0.8 Co 0.1 Mn 0.1 10g of (OH)2 precursor (sheet-like, average thickness approximately 40nm) was added to a lithium source LiOH·H2O and Sm2O3, resulting in a Li:precursor molar ratio of 1.03:1 and a Sm:precursor molar ratio of 0.03:1. The precursor, lithium source, and Sm2O3 were mixed evenly and then placed in a crucible for stepwise sintering. The first step was to raise the temperature from room temperature to 500℃ at a rate of 5℃ / min and hold for 4 hours. The second step was to raise the temperature from 500℃ to 800℃ at a rate of 5℃ / min and hold for 16 hours. After natural cooling, the lithium battery cathode material was obtained.
[0075] (2) Evaluation of lithium battery cathode materials
[0076] The SEM image of the lithium battery cathode material is shown below. Figure 1 As shown in the figure, the preparation method provided by this invention can yield a lithium battery cathode material with good sphericity. This lithium battery cathode material is formed from secondary microspheres created by the stacking of primary particles. The medium particle size of the secondary microspheres is 9.6 μm. Figure 1 The cross-sectional image of the lithium battery cathode material shown is obtained by focused ion beam cutting. Figure 2As shown, the primary particles of the lithium battery cathode material are elongated and arranged radially along the secondary microspheres. The average width of the primary particles is 1.05 μm, and the average aspect ratio of the primary particles is 3.83.
[0077] The above-mentioned lithium battery positive electrode material, acetylene black, and 10% (w / w) polyvinylidene fluoride solution were mixed evenly according to a mass ratio of lithium battery positive electrode material: acetylene black: polyvinylidene fluoride 92:3:5. The mixture was then coated onto aluminum foil, the solvent was dried, and the foil was sliced to obtain the positive electrode sheet. Using a lithium sheet as the counter electrode, the positive electrode sheets were assembled into a coin cell lithium battery in a glove box. The charge / discharge voltage range of the coin cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 205.7mAh / g, with a first-cycle coulombic efficiency of 90.7%. The discharge specific capacity at 1C rate is 179.4mAh / g.
[0078]
Example 2
[0079] This embodiment is used to illustrate the method for preparing and evaluating lithium battery cathode materials according to the present invention.
[0080] (1) Preparation of lithium battery cathode materials
[0081] Take the chemical composition as Ni 0.8 Co 0.1 Mn 0.1 10g of (OH)2 precursor (sheet-like, average thickness approximately 40nm) was added to a lithium source LiOH·H2O and Eu(NO3)3, resulting in a Li:precursor molar ratio of 1.10:1 and an Eu:precursor molar ratio of 0.05:1. The precursor, lithium source, and Eu(NO3)3 were mixed evenly and then placed in a crucible for stepwise sintering. The first step involved heating from room temperature to 500℃ at a rate of 10℃ / min and holding for 6 hours. The second step involved heating from 500℃ to 850℃ at a rate of 10℃ / min and holding for 12 hours, followed by natural cooling to obtain the lithium battery cathode material.
[0082] (2) Evaluation of lithium battery cathode materials
[0083] SEM images of lithium battery cathode materials and Figure 1 Similar to, cross-sectional view and Figure 2 Similar. The primary particles of this lithium battery cathode material are elongated strips, and are arranged radially along the secondary microspheres. The average width of the primary particles is 0.95 μm, and the average aspect ratio is 3.17. The medium particle size of the secondary microspheres is 10.1 μm.
[0084] Lithium batteries were prepared according to the method described in Example 1.
[0085] The charge / discharge voltage range of the button cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 204.5mAh / g, with a first-week coulombic efficiency of 90.6%, and the discharge specific capacity at 1C rate is 178.6mAh / g.
[0086]
Example 3
[0087] (1) Preparation of lithium battery cathode materials
[0088] Take the chemical composition as Ni 0.8 Co 0.1 Mn 0.1 10g of (OH)2 precursor (sheet-like, average thickness approximately 40nm) was added to lithium source LiOH·H2O and Gd(C2H3O2)3, resulting in a Li:precursor molar ratio of 1.05:1 and a Gd:precursor molar ratio of 0.04:1. After the precursor, lithium source, and Gd(C2H3O2)3 were mixed evenly, the mixture was placed in a crucible for stepwise sintering. The first step was to raise the temperature from room temperature to 520℃ at a rate of 5℃ / min and hold for 4 hours. The second step was to raise the temperature from 520℃ to 750℃ at a rate of 10℃ / min and hold for 20 hours. After natural cooling, the lithium battery cathode material was obtained.
[0089] (2) Evaluation of lithium battery cathode materials
[0090] SEM images of lithium battery cathode materials and Figure 1 Similar to, cross-sectional view and Figure 2 Similar. The primary particles of this lithium-ion battery cathode material are elongated strips, and are arranged radially along the secondary microspheres. The average width of the primary particles is 0.84 μm, and the average aspect ratio is 2.85. The medium particle size of the secondary microspheres is 9.8 μm.
[0091] Lithium batteries were prepared according to the method described in Example 1.
[0092] The charge / discharge voltage range of the button cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 202.4mAh / g, with a first-week coulombic efficiency of 90.3%, and the discharge specific capacity at 1C rate is 175.5mAh / g.
[0093]
Example 4
[0094] (1) Preparation of lithium battery cathode materials
[0095] Take the chemical composition as Ni 0.8 Co 0.15 Al 0.0510g of (OH)2 precursor (sheet-like, average thickness approximately 60nm) was added to lithium source LiOH·H2O and Gd(C2H3O2)3, resulting in a Li:precursor molar ratio of 1.10:1 and a Gd:precursor molar ratio of 0.10:1. After the precursor, lithium source, and Gd(C2H3O2)3 were mixed evenly, the mixture was placed in a crucible for stepwise sintering. The first step was to raise the temperature from room temperature to 550℃ at a rate of 5℃ / min and hold for 4 hours. The second step was to raise the temperature from 550℃ to 700℃ at a rate of 10℃ / min and hold for 9 hours. After natural cooling, the lithium battery cathode material was obtained.
[0096] (2) Evaluation of lithium battery cathode materials
[0097] SEM images of lithium battery cathode materials and Figure 1 Similar to, cross-sectional view and Figure 2 Similar. The primary particles of this lithium-ion battery cathode material are elongated strips, and are arranged radially along the secondary microspheres. The average width of the primary particles is 0.68 μm, and the average aspect ratio is 2.56. The medium particle size of the secondary microspheres is 9.7 μm.
[0098] Lithium batteries were prepared according to the method described in Example 1.
[0099] The charge / discharge voltage range of the button-cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 198.3mAh / g, with a first-week coulombic efficiency of 90.0%, and the discharge specific capacity at 1C rate is 174.2mAh / g.
[0100]
Example 5
[0101] (1) Preparation of lithium battery cathode materials
[0102] Take the chemical composition as Ni 0.8 Co 0.1 Mn 0.1 10g of (OH)2 precursor (sheet-like, average thickness approximately 40nm) was added to lithium source LiOH·H2O and Gd(C2H3O2)3, resulting in a Li:precursor molar ratio of 0.95:1 and a Gd:precursor molar ratio of 0.002:1. After the precursor, lithium source, and Gd(C2H3O2)3 were mixed evenly, the mixture was placed in a crucible for stepwise sintering. The first step was to raise the temperature from room temperature to 500℃ at a rate of 5℃ / min and hold for 4 hours. The second step was to raise the temperature from 500℃ to 750℃ at a rate of 10℃ / min and hold for 12 hours. After natural cooling, the lithium battery cathode material was obtained.
[0103] (2) Evaluation of lithium battery cathode materials
[0104] SEM images of lithium battery cathode materials and Figure 1Similar to, cross-sectional view and Figure 2 Similar. The primary particles of this lithium battery cathode material are elongated strips, and are arranged radially along the secondary microspheres. The average width of the primary particles is 0.39 μm, and the average aspect ratio is 1.76. The medium particle size of the secondary microspheres is 10.5 μm.
[0105] Lithium batteries were prepared according to the method described in Example 1.
[0106] The charge / discharge voltage range of the button cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 196.5mAh / g, with a first-week coulombic efficiency of 89.1%, and the discharge specific capacity at 1C rate is 172.7mAh / g.
[0107] Comparative Example 1
[0108] (1) Preparation of lithium battery cathode materials
[0109] Take the chemical composition as Ni 0.8 Co 0.1 Mn 0.1 10g of (OH)2 precursor (sheet-like, average thickness approximately 40nm) was added to a lithium source, LiOH·H2O, to achieve a Li:precursor molar ratio of 1.03:1. The precursor and lithium source were mixed evenly and then placed in a crucible for stepwise sintering. The first step was to raise the temperature from room temperature to 500℃ at a rate of 5℃ / min and hold for 4 hours. The second step was to raise the temperature from 500℃ to 800℃ at a rate of 5℃ / min and hold for 16 hours. After natural cooling, the lithium battery cathode material was obtained.
[0110] (2) Evaluation of lithium battery cathode materials
[0111] The cross-sectional view of the lithium battery cathode material shows that the primary particles are short and coarse, with no specific arrangement and exhibiting a disordered stacking state. The average width of the primary particles is 0.14 μm, and the average aspect ratio is 1.18. The secondary microspheres have a medium particle size of 10.2 μm.
[0112] Lithium batteries were prepared according to the method described in Example 1.
[0113] The charge / discharge voltage range of the button cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 192.1mAh / g, the first-week coulombic efficiency is 87.0%, and the discharge specific capacity at 1C rate is 168.1mAh / g.
[0114] (Comparative Example 2)
[0115] (1) Preparation of lithium battery cathode materials
[0116] Take the chemical composition as Ni 0.8 Co 0.1 Mn 0.1 10g of (OH)2 precursor, the precursor morphology being microspheres formed by primary spindle agglomeration, was added with lithium source LiOH·H2O and Eu(NO3)3, making the molar ratio of Li:precursor 1.10:1 and the molar ratio of Eu to precursor 0.05:1. After the precursor, lithium source and Eu(NO3)3 were mixed evenly, they were placed in a crucible for stepwise sintering. The first step was to heat from room temperature to 500℃ at 10℃ / min and hold for 6h. The second step was to heat from 500℃ to 850℃ at 10℃ / min and hold for 12h, followed by natural cooling to obtain the lithium battery cathode material.
[0117] (2) Evaluation of positive materials for lithium batteries
[0118] The cross-sectional view of the lithium battery cathode material shows that the primary particles are short and coarse, with no specific arrangement and exhibiting a disordered stacking state. The average width of the primary particles is 0.18 μm, and the average aspect ratio is 1.27. The secondary microspheres have a medium particle size of 10.1 μm.
[0119] Lithium batteries were prepared according to the method described in Example 1.
[0120] The charge / discharge voltage range of the button cell lithium battery is 2.8-4.3V. The initial discharge specific capacity at 0.1C rate is 191.3mAh / g, the first-week coulombic efficiency is 87.1%, and the discharge specific capacity at 1C rate is 166.3mAh / g.
[0121] Table 1. Electrochemical performance test results of lithium batteries obtained in each example.
[0122]
[0123] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A lithium battery cathode material, wherein the general chemical formula of the cathode material is Li a Ni x Co y M z N p O2, where, 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, and the values of a, x, y, z, and p satisfy the principle of electroneutrality. M is selected from at least one element of Group VIIB or Group IIIA, and N is selected from at least one of the lanthanide elements. The primary particles of the positive electrode material are strip-shaped, and the width of the strip is 0.15 - 5.00 μm.
2. The lithium battery cathode material according to claim 1, characterized in that, The chemical general formula of the positive electrode material is Li a Ni x Co y M z N p O2, where 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.
05. Among them, x, y, and z do not take the value of 0 simultaneously. Preferably, the values of x, y, and z are not 0, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality.
3. The lithium battery cathode material according to claim 1, characterized in that, The width of the strip is 0.20 - 5.00 μm, preferably 0.30 - 3.00 μm.
4. The lithium battery cathode material according to claim 1, characterized in that, The morphology of the positive electrode material is secondary microspheres formed by the aggregation of primary particles, where the primary particles are arranged along the radial direction of the secondary microspheres; Preferably, the aspect ratio of the primary particles is 1.05 - 15.00, preferably 1.30 - 10.00, and more preferably 1.50 - 8.00; Preferably, the median size of the secondary microspheres is 1.0 - 20.0 μm.
5. The method for preparing the lithium battery positive electrode material according to any one of claims 1 - 4, comprising: Mixing a positive electrode material precursor, a lithium source, and a modifier containing a lanthanide element, and sintering to obtain the lithium battery positive electrode material.
6. The preparation method according to claim 5, characterized in that, The general chemical formula of the cathode material precursor is Ni. x Co y M z (OH)2, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, and the values of x, y and z are not simultaneously 0, and the values of x, y and z satisfy the principle of electroneutrality; And / or, the morphology of the positive electrode material precursor is microspheres formed by stacking flakes; the average thickness of the flakes is 1 - 500 nm, preferably 10 - 300 nm.
7. The preparation method according to claim 5, characterized in that, The lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium acetate, and lithium oxalate; And / or, the modifier containing a lanthanide element is selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates, and oxalates containing lanthanide elements.
8. The preparation method according to claim 5, characterized in that, The molar ratio of the positive electrode material precursor to the lithium source in terms of Li element is 1:(0.90 - 1.20); And / or, the molar ratio of the positive electrode material precursor to the modifier containing a lanthanide element in terms of lanthanide element is 1:(0 - 0.10) and not 0, preferably 1:(0.001 - 0.05).
9. The preparation method according to claim 5, characterized in that, The sintering temperature is 600 - 1000 °C, preferably 720 - 900 °C, and the sintering time is 4 - 48 h, preferably 8 - 24 h, and more preferably 12 - 20 h.
10. The application of the lithium battery positive electrode material according to any one of claims 1 - 4 in a lithium battery.
Citation Information
Patent Citations
Preparation method of carbon-coated ternary cathode material and the carbon-coated ternary cathode material
CN103474628B
Preparation method of carbon nitride nanotube-modified high rate performance nickel-cobalt-manganese ternary positive material
CN104993100A
Directional alignment high-nickel ternary positive electrode material and preparation method thereof
CN108054354A
High-nickel positive electrode material with primary particles being directionally arranged, and preparation method for high-nickel positive electrode material
CN109713297A
Pressure-resistant positive electrode active material and electrochemical energy storage device
CN111384371A